2014
DOI: 10.1007/s12185-014-1699-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of serum erythropoietin levels in Japanese patients with myelodysplastic syndromes

Abstract: Erythropoiesis-stimulating agents (ESAs) are used to ameliorate anemia in lower-risk myelodysplastic syndromes (MDS). Serum erythropoietin (EPO) level <500 IU/L is widely accepted as a major predictive factor for response to ESAs. However, few data about EPO levels in the Japanese population are available. We therefore evaluated distribution of serum EPO levels in Japanese patients with MDS. Forty-three cases were analyzed; 30 were classified as lower-risk MDS (low or intermediate-1 by the international progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Similar results were also obtained in studies abroad, although the EPO levels increased up to~100 mIU/mL in some patients with stage 3 CKD [5,6]. In contrast, EPO levels were >50 mIU/mL in most patients with hematological diseases [3,4].…”
Section: Rationalesupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were also obtained in studies abroad, although the EPO levels increased up to~100 mIU/mL in some patients with stage 3 CKD [5,6]. In contrast, EPO levels were >50 mIU/mL in most patients with hematological diseases [3,4].…”
Section: Rationalesupporting
confidence: 86%
“…In these reports, most patients with hematopoietic disorders such as aplastic anemia and myelodysplastic syndromes (MDS) with Hb levels of <10 g/dL showed serum EPO levels of >50 mIU/ mL [by radioimmunoassay or the chemiluminescent enzyme immunoassay (CLEIA)] [3,4], whereas most CKD patients showed serum EPO levels of <50 mIU/mL [by enzyme-linked immunosorbent assay (ELISA) or the CLEIA method] [5,6] (different measurement methods may affect the measured value of EPO, but such an effect has not been examined). Moreover, it has been reported that the increase in EPO level in response to the decrease in Hb level is suppressed at more advanced stages of CKD [6].…”
Section: )mentioning
confidence: 99%
“…Conversely, elevating sEPO levels with ESAs is more likely to be beneficial among patients with lower levels. Some studies have shown that sEPO levels have a strong inverse correlation with hemoglobin levels in lower-risk MDS patients [35,75], suggesting that patients with worse anemia (i.e., lower hemoglobin) may have higher levels of sEPO. Patients who are resistant to ESAs have higher sEPO and lower hemoglobin levels than those who respond (Tables 1 and 2), so these factors may be indicative of reduced bone marrow responsiveness.…”
Section: Rationale For the Predictive Value Of Sepomentioning
confidence: 99%
“… 27 However, the erythroid response is observed in a relatively low number of patients and often not sustained, 28 which is in part due to endogenously elevated erythropoietin levels because of ineffective erythropoiesis in many patients. 29 We speculated that a sustained endogenous elevation of erythropoietin levels or iatrogenic erythropoietin therapy in MDS patients might contribute to the dysregulation of the osteo-hematopoietic niche, at least partly due to its effects on MSC and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%